Effect of Jogging Duration on Concentration Levels among University Students - Amadeo Wibisono; Aila Johanna; Julia Rahadian Tanjung; Nawanto Agung Prastowo; Ignatio Rika Haryono (Faculty of Medicine Universitas Padjadjaran, 2026)
Background: Concentration is an important component of cognitive function. However, many college students experience reduced attention spans, often lasting only 10 to 15 minutes. Previous studies have shown that poor concentration levels remain common among university students. Physical exercise, such as jogging, may improve brain function and enhance concentration. This study aimed to evaluate the influence of jogging duration on concentration levels among university student. Methods: This experimental study was conducted in 2024, involving medical students from a university in Jakarta, Indonesia. Participants were screened using the Physical Activity Readiness Questionnaire (PAR-Q) and selected through random sampling. Respondents were divided into three groups: a 10-minute jogging group, a 30-minute jogging group, and a control group without jogging intervention. The intervention was conducted for 8 weeks at each participant’s location. Concentration levels were assessed before and after the intervention using the Concentration Grid Test, administered at the university. Data were analyzed using ANOVA to compare changes in concentration scores and the Kruskal-Wallis to compare post-intervention scores among groups.Results: A total of 28 students participated, with females comprising the majority of participants (64.3%; n=18). The 10-minute jogging group demonstrated a significant improvement in concentration levels compared with the control group (p=0.004). Concentration Grid Test scores increased by 4.6 points in the 10-minute jogging group (p<0.001), and by 3.8 points in the 30-minute jogging group (p=0.003). Conclusions: A 10-minute jogging session improves concentration levels among university students, suggesting that short-duration physical activity provide cognitive benefits and may support academic performance and well-being.